Improving Students’ Speaking Skills through the Use of Video-Based Scientific Approach - Ardiansyah Ardiansyah (Universitas Pendidikan Mandalika, 2020)
The objective of this classroom action research (CAR) was to improve the students’ speaking skills through video based scientific approach at class XI MIPA 1 SMAN 9 Mataram in the Academic Year of 2019/2020. The CAR was conducted in two cycles. Each cycle consisted of three meetings. The steps were reconnaissance, planning, action and observation, and reflection. The researcher worked collaboratively with the English teacher and the students. The data collected were in the forms of qualitative. The qualitative data were gained through observing, interviewing the English teacher and students, and taking photographs. The data were in the forms of vignettes, interview transcripts, and photographs. In addition, this research implemented five criteria of validity namely democratic validity, dialogic validity, outcome validity, process validity, and catalytic validity. To get the trustworthiness, the researcher used some triangulation principles such as time triangulation and investigator triangulation. The results of this research showed that using videos based on scientific approach in the teaching and learning of speaking was proved to improve the students’ speaking skills in five aspects: vocabulary, pronunciation, grammar, fluency, and comprehension. The students were more enthusiastic in learning speaking. They could actively involve in the speaking learning process. Moreover, the students were more confident and fluent in speaking practices.